Rape and Murder among Refugees: A Crisis Point for Europe’s Immigration Policy? - Hedges, Paul (2016)
Recent criminal incidents involving rape or murder allegedly by new immigrants is creating dissatisfaction with the welcome given to refugees and stoking right-wing populism and Islamophobia. Europe’s politicians need to carefully balance law and order and immigration, but not give way to anti-immigrant and Islamophobic sentiments.